CYP3A5 and ABCB1 polymorphisms in living donors do not impact clinical outcome after kidney transplantation. (11th July 2018) - Yang, Lin; de Winter, Brenda CM; van Schaik, Ron HN; Xie, Rui-Xiang; Li, Yi; Andrews, Louise M; Shuker, Nauras; Bahmany, Soma; Koch, Birgit; van Gelder, Teun; Hesselink, Dennis A
Aim: To investigate the association between donor CYP3A5 and ABCB1  polymorphisms and tacrolimus (Tac)-induced nephrotoxicity and renal function in kidney transplant recipients.Methods: The CYP3A5 6986A>G and ABCB1 3435C>T polymorphisms were determined in 237 recipients and donors.Results: There was no significant association between Tac-related nephrotoxicity and donor CYP3A5 and ABCB1 genotype. The donor ABCB1 3435C>T polymorphism was associated with estimated glomerular filtration rate on day 7 and month 1. The combined donor–recipient ABCB1 genotype (3435C>T polymorphism) was significantly related with estimated glomerular filtration rate on day 3 and 7 in univariate analysis. However, these differences were no longer statistically significant in multivariate analysis.Conclusion: A genetic analysis of ABCB1 and CYP3A5 of kidney transplant donors is not helpful to improve renal transplant outcomes.